IgE binding capacity of apple allergens preserved after high pressure treatment - Fernández, Avelina; Butz, Peter; Tauscher, Bernhard (High pressure research, 2009)
Two strategies were performed to assay the antigenicity of an apple extract (Golden Delicious) after combined pressure/temperature treatments using pools of sera of patients with positive serum IgE to apple. The IgE binding capacity of SDS denatured proteins was tested after electro-transference to membranes. Additionally, competitive RAST inhibition tests were carried out with the native apple proteins. Antigenicity was also assessed after 10 months of storage. In general, the results with sera of Spanish patients obtained by the RAST inhibition method confirmed the negligible effects of high pressure treatments up to 800 MPa on apple antigenicity and IgE binding, similarly to other European populations. Immunoblots revealed, contrarily, that heat is more important than pressure in inducing irreversible changes in key epitopes. Furthermore, pressure treatments (up to 800 MPa) preserved inhibition scores in frozen apple extracts closer to the untreated controls during at least 10 months, which could be relevant in the design of strategies to preserve allergen antigenicity.
Gesehen am 03.01.2023